Au-Doped PtAg Nanorod Array Electrodes for Proton-Exchange Membrane Fuel Cells - Fidiani, Elok; Du, Shangfeng; AlKahfi, Ahmad Zubair; Absor, Moh Adhib Ulil; Pravitasari, Ratna Deca; Damisih, Damisih (ACS Publications, 2022)
One-dimensional Pt-based alloy nanostructures have been demonstrated as highly active and durable catalysts for an oxygen reduction reaction (ORR), which are the key to achieving the sustainability of proton-exchange membrane fuel cells (PEMFCs). However, the high difficulty in the fabrication of a practical catalyst electrode based on these nanostructures has limited their potential for PEMFC applications. In this work, we demonstrate a facile approach of Pt-alloy nanorod (NR) array gas diffusion electrodes (GDEs) through in situ growth on a carbon paper gas diffusion layer and Au doping utilizing a one-step wet chemical reduction method. The GDE is directly used as the cathode in PEMFCs. The excellent catalytic activity of the Au-doped PtAg NRs and the promoted mass transport characteristics of the array electrode structure enable an enhanced power density of 1.1-fold with an even 30 wt % less Pt loading, compared to the GDEs made of monometallic Pt NR arrays and commercial Pt/C. Density functional theory prediction reveals the increased ORR kinetics resulting from the weakening binding energy toward oxygen-containing species on the surface of Au-doped PtAg. The Au stabilizing effect to minimize the atomic segregation between Pt and Ag is also investigated theoretically and experimentally based on the accelerated degradation test under the fuel cell operating condition.